SDGs DISCLOSURE DEPENDENCY ON INFORMATION ASYMMETRY TO REDUCE FIRMS’ STOCK VOLATILITY - Kamil, Irham; Saraswati, Erwin; Adib, Noval (JRAK, 2026)
Motivated by limited SDGs financing and largely symbolic corporate engagement in Indonesia, concerns arise regarding how SDGs disclosure relates to stock volatility. This study examines the effect of SDGs disclosure on stock volatility and the role of information asymmetry, with SDGs disclosure decomposed into depth, breadth, and concentration. This quantitative study uses firms in the ESGQ KEHATI Index over 2020–2024, resulting in 197 firm-year observations and analyzed using panel regression. The findings indicate that SDGs disclosure tends to reduce stock volatility, although this effect depends on information asymmetry. At the dimensional level, depth is associated with higher volatility, while breadth and concentration show an inverse relationship. These findings provide empirical insights into the role of SDGs disclosure in capital market dynamics and contribute to the limited literature in Indonesia.